Chemical studies of high molecular weight fractions of Nigerian bitumen. (March 2015) - Adebiyi, F.M.; Odunlami, A.; Thoss, V.
Highlights: Analysis gives insight to characteristics which may assist in Nigerian bitumen development. Analysis for compound types using Fourier Transform Infrared (FT-IR) spectrometer. Elemental analysis using ICP-OES and carbon/nitrogen analyzer. Catalytic poisoning and environmental degradation are likely during the bitumen exploitation. Abstract: Chemical analysis of high molecular weight fractions of Nigerian bitumen was carried out to ascertain their characteristics which may assist in the development of the natural resource. Bitumen samples were fractionated by silica gel column chromatography into aromatics and nitrogen, sulphur, oxygen (NSO) compounds fractions. The fractions were analyzed for compound types using Fourier Transform Infrared (FT-IR) spectrometer. The elemental analysis of NSO compounds fraction was done using Inductively Coupled Plasma-Optical Emission Spectrometer (ICP-OES) and carbon/nitrogen analyzer. The FT-IR analysis results obtained for NSO compounds fraction showed IR peaks of the following functional groups: C–H (CH3 ), C–H (CH2 ), CC, C–O, CO, N–H, C–O–C, CS, C–N, SO, suggesting the presence of mixtures of paraffinic, aldehydric, anhydic, naphthenic, and heteroatoms containing compounds, while the results on aromatic fraction follow the same trend except for the absence of CS CO and C–N. The results showed higher elemental concentrations in the NSO fraction than the whole Nigerian bitumen and was confirmed by their calculated T -test values. The results also indicated that V/Ni ratio for the NSO fraction increased with the age of the producing field. Strong and positive correlations exist between most of the analyzed elements and were confirmed by the expected geochemical relationships between the sample locations as revealed by the result of cross plot analysis. The overall results indicated that refining of the bitumen may experience catalytic poisoning and its exploitation may also cause environmental degradation as well as intrinsic health hazard, considering the cumulative effect of the analyzed chemicals in ecosystems.